Challenges to the Sustainability of Small, Medium, and Micro-Enterprises (SMMEs) in the Cape Metropolis - Akpo, Martin Ndutu Aka; Ogunlela, Oyebanjo, G.; Tengeh, Robertson, K.; Tengeh, Laura N. (Reshaping Sustainable Development Goals Implementation in the World: Proceeding of 7th International Conference on Business and Management Dynamics, 2021)
It is widely acknowledged that SMMEs contribute substantially to job creation and economic development in South Africa, making them a critical component of the nation's economic transformation strategy in terms of job creation and contribution to Gross Domestic Product (GDP). This conceptual paper examines the factors that inhibit the long-term survival of Small, Medium and Micro Enterprises (SMMEs) in the Cape metropolis through a literature review. It then applied the idea of newness to SMMEs and examined the many obstacles impeding their sustainability. Emanating from internal and external sources, these obstacles include limited access to sufficient finance and lack of skills to handle contemporary businesses financial and IT needs. This study concludes that further empirical research is necessary to ascertain their effect on economic growth and business sustainability. Additionally, it is proposed that national and provincial governments establish business incubators (BI) to assist SMMEs in becoming more sustainable.